(untitled) (Journal of Fatima Jinnah Medical University, 2024)
Background: Students learn through peer learning; it is one of the central learning approaches. Peer learning inspires students to teach and learn from each other. The objective of the study was to determine the relationship between peer versus non-peer group learning and the academic performance of nursing students (NS). Methods: A correlational research design was conducted at two public sectors: Dow Institute of Nursing and Midwifery Karachi and College of Nursing Dr. Ruth K. M. Pfau Civil Hospital Karachi. Three hundred NS were included in the study through purposive sampling techniques and the study duration was four months (December 2022 to March 2023). The inclusion criteria were undergraduate NS who were acquainted with peer learning. Those NS who were not present at the time of data collection were excluded from the study. According to the study’s objectives, a questionnaire was developed by reviewing previous studies. Data was entered and analyzed on SPSS version 26. Results: Out of 300, n=156(52%) were from peer group and n=144(48%) were from non-peer-group and n=167(55.7%) had reported good performance (>3 GPA) and n=133(44.3%) reported average performance (≤3 GPA) at academic. Both groups of NS showed significant differences in academic performance (P- value <0.05). The peer group of NS has found a positive correlation (r.1.000) and is highly significant (P- value <.005) with academic performance. Conclusion: The current study concluded that most NS belonged to peer groups, and more than half of the NS attained good academic performance. Peer groups also showed a positive correlation and high significance with academic performance.